BANKS AND FINTECH: IMPACT OF TECHNOLOGICAL INNOVATION ON COMPETENCES MANAGEMENT IN LATVIA - Nātriņš, Andris; Sarnovics, Andris; Miķelsone, Elīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Purpose: To explore information and communication technologies (ICT) impact on competences management in the financial sector in Latvia.Methodology: Focus group discussion with leading financial sector experts in the Latvia.Findings: There is a mismatch between academically provided competences and what is expected by the financial sector representatives within Latvia.Originality/value: Empirical research on what kind of competences are important in the financial sector at present and in the future. Contribute to the current literature by researching on how resulting competencies from the focus group compare to the academically provided competences for potential financial sector employees. By exploring received responses to the questions from this research, it can help policymakers, financial sector and academical representatives to stay agile to the arising changes of supplied and demanded competencies in the financial sector.